Reshaping Engineering Education Addressing Complex Human Challenges - Habbal, Fawwaz (Springer Nature, 2024)
This open access book is dedicated to exploring methods and charting the course for enhancing engineering education in and beyond 2023. It delves into the idea that education, coupled with social connections, is indispensable for a more profound comprehension of the world and the creation of an improved quality of life. The book serves as a conduit for incorporating complex problem-solving into engineering education across various formats. It offers a structured approach for tackling complex issues, comparing an array of techniques for managing complexity within the realm of engineering education. Moreover, the book scrutinizes several complex case studies derived from the United Nation's Sustainable Development Goals. Additionally, it explores intricate problem-solving and curriculum change case studies specific to engineering education from Harvard University, the University of Technology Sydney, and Aalborg University.